The Role of Physical Education Teachers in Improving Emotional and Spiritual Intelligence of Students at SMK Negeri 1 Bima - Sunardin, Sunardin; Furkan, Furkan; Salahudin, Salahudin; Suherman, Suherman (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. This study seeks to examine the role of Physical Education (Penjas) instructors in enhancing the emotional and spiritual intelligence of students at SMK Negeri 1 Bima. Emotional intelligence encompasses an individual's capacity to identify, comprehend, and regulate their own emotions as well as those of others, whereas spiritual intelligence pertains to the ability to grasp the significance and purpose of life and cultivate elevated moral values. Both forms of intelligence are crucial in shaping students' character, which ultimately influences their achievement in numerous domains of life, including academic and social spheres. Materials and Methods.The employed research method is qualitative, utilising a descriptive approach. Data were gathered via direct observation in the Physical Education class, comprehensive interviews with educators and students, and examination of documentation pertaining to the curriculum and extracurricular activities organised by the institution. The study participants included Physical Education teachers and eleventh-grade students at SMK Negeri 1 Bima. Data collection occurred during one academic semester, enabling researchers to acquire a thorough understanding of the interaction between teachers and students within the realm of Physical Education learning. Results. The study's findings demonstrate that physical education instructors play a crucial role in fostering students' emotional intelligence. This is accomplished through many pedagogical methodologies that incorporate self-regulation exercises, stress management techniques, and collaborative teamwork skills. Physical education instructors additionally promote learning that fosters empathy, the capacity to comprehend others' viewpoints, and proficient communication skills. Conclusion. This study demonstrates that physical education teachers can serve as comprehensive character educators, emphasising not only physical development but also emotional and spiritual growth in children. This underscores the significance of holistic and integrative physical education in fostering the development of well-rounded character in students.